Bacteriophages as biocontrol agents of food pathogens - Mahony, Jennifer; M cAuliffe, Olivia; Ross, R Paul; van Sinderen, Douwe (Current opinion in biotechnology, 2011)
Bacteriophages have long been recognized for their potential as biotherapeutic agents. The recent approval for the use of phages of Listeria monocytogenes for food safety purposes has increased the impetus of phage research to uncover phage-mediated applications with activity against other food pathogens. Areas of emerging and growing significance, such as predictive modelling and genomics, have shown their potential and impact on the development of new technologies to combat food pathogens. This review will highlight recent advances in the research of phages that target food pathogens and that promote their use in biosanitation, while it will also discuss its limitations.